Boosting Multiverse Optimizer by Simulated Annealing for Dimensionality Reduction - Mutlag, Wamidh K.; Mazher, Wamidh Jalil; Ibrahim, Hadeel Tariq; Ucan, Osman Nuri (Universitas Airlangga, 2025)
Because of its dynamic graph structure and exceptional global/local search abilities, the Multiverse Optimizer (MVO) is widely used in feature selection. The exponential growth of the search space makes finding the optimum feature subset for numerous dimensional datasets quite challenging. Despite that MVO is a promising algorithm, the sluggish convergence issue affects the multi-verse optimizer performance. This work focuses on hybridizing and boosting MVO with the powerful local search algorithm, Simulated Annealing algorithm (SAA), in order to get around MVO limitations and enhance feature selection efficiency in high dimensional datasets. Stated differently, a paradigm known as high-level relay hybrid (HRH) is put forth that sequentially implements self-contained optimization (i.e. MVO and SAA). As a result, the optimal regions are found by MVO and then supplied to SAA in the suggested MVOSA-FS model. Ten high-dimensional datasets obtained from the Arizona State University (ASU) repository were used to verify the effectiveness of the proposed method; the results are compared with other six state-of-the-art feature selection algorithms: Atom Search Optimization (ASO), Equilibrium Optimizer (EO), Emperor Penguin Optimizer (EPO), Monarch Butterfly Optimization (MBO), Satin Bowerbird Optimizer (SBO), and Sine Cosine Algorithm (SCA). The results validate that the proposed MVOSA-FS technique performed better than the other algorithms and showed an exceptional ability to select the most significant and optimal features. The lowest average error rates, classification standard deviation (STD) values, and feature selection (FS) rates are obtained by MVOSA-FS across all datasets.